2010
DOI: 10.1002/dvdy.22428
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Hand1 cell lineage reveals novel contributions to cardiovascular, neural crest, extra‐embryonic, and lateral mesoderm derivatives

Abstract: The basic Helix-Loop-Helix (bHLH) transcription factors Hand1 and Hand2 play critical roles in the development of multiple organ systems during embryogenesis. The dynamic expression patterns of these two factors within developing tissues obfuscate their respective unique and redundant organogenic functions. To define cell lineages potentially dependent upon Hand gene expression, we generated a mutant allele in which the coding region of Hand1 is replaced by Cre recombinase. Subsequent Cre-mediated activation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(107 citation statements)
references
References 33 publications
4
103
0
Order By: Relevance
“…X-Gal staining of whole-mount and sectioned embryos was performed as described (7,10). All embryo sections are transverse unless otherwise indicated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…X-Gal staining of whole-mount and sectioned embryos was performed as described (7,10). All embryo sections are transverse unless otherwise indicated.…”
Section: Methodsmentioning
confidence: 99%
“…Cre knock-in allele provides a tool with which to interrogate cellautonomous roles of Hand factors within the MD1 (7,8). To examine the development of the H1 lineage relative to the developing incisors, we performed X-Gal staining of R26R lacZ/+ ;H1 Cre/+ embryos at E15.5.…”
Section: The H1mentioning
confidence: 99%
“…As these CPCs become further specified into each of the cardiovascular cell types, they undergo extensive transcriptional changes associated with their cell type as well as their anatomical position within the developing heart. However, beyond a few well-recognized markers such as Hand1 and Tbx5 for the inflow tract and left ventricle (Barnes et al, 2010; Bruneau et al, 1999); Isl-1 and Sema3c for the outflow tract (Feiner et al, 2001; Sun et al, 2007); Tbx2/3 for the AVC (Christoffels et al, 2004); and Pitx2 for the left atrium (Liu et al, 2002), there are relatively few validated markers that distinguish cells from different regions of the developing heart.…”
Section: Introductionmentioning
confidence: 99%
“…First, this protocol provides a common differentiation platform for deriving cardiac and endothelial lineages through simple modulation of activin A and BMP4 concentrations. Second, developmental studies have shown distinct origins and mechanisms for specifying endothelial subtypes such as endocardial, vascular, and lymphatic ECs 2025 . To this end—using an approach of polarizing hPSC mesoderm at the onset of differentiation—this protocol provides the first approach for controlling EC differentiation from cardiogenic versus hemogenic mesoderm.…”
Section: Introductionmentioning
confidence: 99%